Increased levels of sirtuin‐1 in systemic lupus erythematosus. (29th May 2022) - Yang, Chan; Li, Rong; Xu, Wang‐Dong; Huang, An‐Fang
Abstract: Aim: We investigated plasma sirtuin‐1 (SIRT1) levels in systemic lupus erythematosus (SLE) patients, and discussed potential of plasma SIRT1 as a biomarker for SLE. Methods: A total of 359 subjects, including 299 patients (89 SLE, 50 rheumatoid arthritis, 30 osteoarthritis, 30 gout, 38 Sjögren's syndrome, 20 ankylosing spondylitis, 30 mixed connective tissue disease, 12 systemic sclerosis) and 60 healthy controls were recruited. SIRT1 in plasma of SLE patients was detected by enzyme‐linked immunosorbent assay. Relationship between SIRT1 levels, clinical, laboratory characteristics in SLE patients was discussed. Plasma SIRT1 to discriminate SLE from different rheumatic patients and healthy controls was assessed by receiver operating characteristic (ROC) curve analysis. Results: SIRT1 levels were elevated in SLE patients compared with healthy controls (6.28 [5.89‐6.68] vs 2.42 [2.10‐2.74] ng/mL, P < .001). SIRT1 concentration in plasma was significantly associated with disease activity ( r s = .317, P < .001). Area under the ROC curve (AUC) analysis showed that compared to healthy controls, SIRT1 had a good ability for diagnosis of SLE (AUC = 0.986, P < .001). Compared with rheumatoid arthritis, osteoarthritis, Sjögren's syndrome, ankylosing spondylitis, mixed connective tissue disease and systemic sclerosis patients, the AUC of plasma SIRT1 in SLE patients was 0.982, 0.881, 0.810, 0.860, 0.781, 0.889, 0.736, respectively. When evaluating the discriminative power of SIRT1, the sensitivity and specificity for distinguishing SLE from non‐SLE patients were 95.51%, 61.43%, respectively, at the optimal cut‐off value of 4.323 ng/mL. Conclusion: Circulating SIRT1 was elevated in SLE, and might be a promising SLE diagnostic marker.